A infrajustiça no juizado de paz: um estudo sobre as competências e atribuições dos juízes de paz em Cachoeira do Sul no século XIX - Alves, Viviane Siqueira (2023)
The court of the peace was an institution founded in Brazil in 1827, of elective character, lay and of local action, which has a rich historiography that deals with institutional aspects and the trajectories of judges in different spaces.This linked to the research line Frontier, Politics and Society of the Graduate Program in History of the Federal University of Santa Maria work addressed the court of the peace in Cachoeira do Sul, a space not yet contemplated by research on the subject, in the period from 1827 to 1845, searching to analyze institutional and professional biographical aspects of the subjects who occupied this position in the period selected for analysis. In this analysis, understanding the performance of the Court of the Peace involves conceiving them as a judicial and elective institution that, because of their local character and great autonomy, operated in a hybrid space between the official and the informal. In this way , the concept of infrajustice will be used to understand the role played by these lay judges , serving to ponder the dimensions of action of our study project. From the approach of the historical context of the institution and of the same in Cachoeira do Sul, it presents the mapping of the individuals who passed through the position. In this sense, from the name and using prosopography resources, it was possible to access general biographical data, as well as professional aspects of the individuals, also perceiving the circulation for other positions and activities. In addition, observing the years in which it was possible to map judges working in Cachoeira do Sul, I dedicated myself to starting a discussion about the application of the Court of the Peace legislation, comparing it with data presented for other locations.